Urgensi Manajemen Sumber Daya Insani Pada Industri Halal - Nuntupa, Nuntupa; Saleem, Saleem (Finance : Journal of Accounting and Finance, 2023)
Today the halal industry is in a significant upward trend, ranging from banking, travel, fashion to other businesses. Of course this requires the best plan to support the increase in the halal industry in Indonesia, especially in the field of human resources. This paper uses a literature review of relevant references related to the urgency of human resource management in the halal industry. The importance of human resource development in the development of the halal industry is needed to encourage the development of the halal industry so that it can compete with conventional industries.